2018
DOI: 10.1088/1755-1315/105/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel synthesis from nannochloropsis oculata and chlorella vulgaris through transesterification process using NaOH/zeolite heterogeneous catalyst

Abstract: Abstract. Microalgae are promising sources of biofuel due to its production capacity of lipid that can be utilized as raw material for biodiesel production, especially Nannochloropsis oculata and Chlorella vulgaris. The lipid produced can be converted into biodiesel through transesterification reaction using homogenous or heterogeneous catalysts. Heterogeneous catalysts are more advantageous than homogeneous catalysts due to its solid form that eases the separation of catalysts from the products. In this resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Indeed, the selected mutant exhibited an increased lipid productivity in +N condition of ~ 80% compared to WT on a volumetric base. This trait is interesting considering the strong increased in C16:0, C16:1, C18:0 and C18:1 without the energetic and economic costs of inducing nutrient starvation, and their possible use for biodiesel production [57,58]. Improved photosynthetic efficiency by manipulating chlorophyll per cell content is thus a suitable strategy to increase lipid productivity in N. gaditana.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the selected mutant exhibited an increased lipid productivity in +N condition of ~ 80% compared to WT on a volumetric base. This trait is interesting considering the strong increased in C16:0, C16:1, C18:0 and C18:1 without the energetic and economic costs of inducing nutrient starvation, and their possible use for biodiesel production [57,58]. Improved photosynthetic efficiency by manipulating chlorophyll per cell content is thus a suitable strategy to increase lipid productivity in N. gaditana.…”
Section: Discussionmentioning
confidence: 99%
“…Microalgae are considered ideal biomass materials for the production of thirdgeneration biofuels due to their faster growth rate, ability to thrive in non-arable terrestrial or aquatic environments, and higher lipid productivity [40]. Lipids obtained from microalgae can be transformed into biodiesel through transesterification reactions using heterogeneous or homogeneous catalysts [41]. Our study's comparative analysis of lipid concentrations in microalgae groups revealed that the highest value was recorded in Chlorella vulgaris, followed by local microalgae (Figure S1).…”
Section: The Likelihood Of Biodiesel Productionmentioning
confidence: 85%
“…Microalgae are considered prominent sources of biofuel due to their higher levels of lipid production, and can be used as raw material for biodiesel production. Sistiafi and Putri [41] noted that biodiesel yields produced from the lipids of Chlorella vulgaris were better than those from Nannochloropsis oculate [41], while Aguoru and Okibe [42] reported that oil extracted from Chlorella vulgaris contained unsaturated and saturated fatty acids, with the most abundant chain lengths being C9:0, 10:0, 13:0, 16:0, 18:0, 8:1, and 18:2, with C18:1 dominating. They also established Chlorella vulgaris.…”
Section: The Likelihood Of Biodiesel Productionmentioning
confidence: 99%
“…The study optimized the transesterification process using response surface methodology (RSM) and achieved a biodiesel yield of 92.03% under optimal conditions [74]. Jazie et al [75] achieved higher yields of biodiesel through in-situ transesterification using dodecylbenzenesulfonic acid as a catalyst, highlighting its efficiency in reducing the cost of biodiesel production. The in-situ transesterification process yielded larger amounts of biodiesel compared to the two-step extraction-transesterification procedure.…”
Section: Transesterification For Biodiesel Production and Catalystsmentioning
confidence: 99%